2011
DOI: 10.1007/s13353-011-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Small supernumerary marker chromosome (sSMC) derived from chromosome 22 in an infertile man with hypogonadotropic hypogonadism

Abstract: We describe the first case of a supernumerary inv dup(22)(q11.1) in an infertile male with hypogonadotropic hypogonadism. This case supports the opinion that supernumerary inv dup(22)(q11.1) could play a role in male infertility. We suggest that the breakpoint in the region 22q11.1 and/or fourfold dosage of centromeric/pericentromeric sequences of the chromosome 22 may be the cause of hypogonadotropic hypogonadism resulting in impaired spermatogenesis and infertility in our patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Translocations involving an acrocentric chromosome have been thought to be more harmful for the fertility of the carrier than translocations not involving acrocentric chromosomes because of the tendency of acrocentric chromosomes to associate with the sex body (Mikelsaar et al 2011;Oliver-Bonet et al 2005). The translocation t (5;13) in our patient has the breakpoint at 13q12.1, where more than 120 genes have been localized.…”
Section: Discussionmentioning
confidence: 73%
“…Translocations involving an acrocentric chromosome have been thought to be more harmful for the fertility of the carrier than translocations not involving acrocentric chromosomes because of the tendency of acrocentric chromosomes to associate with the sex body (Mikelsaar et al 2011;Oliver-Bonet et al 2005). The translocation t (5;13) in our patient has the breakpoint at 13q12.1, where more than 120 genes have been localized.…”
Section: Discussionmentioning
confidence: 73%
“… [4] On the other hand, the existence of euchromatin in the sSMC often had a detrimental effect on abnormal phenotypes while the duplication of heterochromatin in sSMC were harmless. [ 9 13 ]…”
Section: Discussionmentioning
confidence: 99%
“… [15] As for sSMC(22), 80% carriers were identified as non-mosaic dicentric duplications involving the euchromatic region 22q11.2, such as derivative chromosome 22 (der (22)t (11;22)(q23;q11.2)), cat-eye syndrome (inv dup (22q)). [ 9 16 ] And previous reports indicated that acrocentric sSMC was predominant in subfertile population, especially the chromosome 15, 14, and 22. [17]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatozoa bearing abnormal chromosomes may cause abnormal embryonic development, with poor cardiac activity, which can in turn, cause early pregnancy loss [30,31]. However earlier reports suggest the presence of this small bi-satellited chromosome 22 with the impaired spermatogenesis and male infertility due to the four fold dosage of centromeric sequences -this holds true for the male partner with marked oligospermia [32]. The presence of this small abnormal chromosome entity in the karyogram does not show any phenotypic abnormality or any other IQ related developmental variations in the individual as he is a wellqualified working professional.…”
Section: Discussionmentioning
confidence: 99%